2021
DOI: 10.1186/s41043-021-00275-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence to anti-TB treatment and associated factors among adult TB patients in Gondar city administration, Northwest, Ethiopia: based on health belief model perspective

Abstract: Background Adherence is crucial in treating Tuberculosis to achieve the required treatment success rate. However, due to the longer treatment duration, adherence to Tuberculosis treatment is the most challenging factor affecting Tuberculosis control. Furthermore, although several studies have reported the determinants of Tuberculosis treatment adherence, few of them have used Health Belief Model (HBM) as the guiding principle to determine the individual perception of health-related decisions as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(53 reference statements)
0
7
1
1
Order By: Relevance
“…The 84.6% adherence rate observed in this study is lower than the 90% targeted by the national TB and leprosy program (USAID, 2022). Our findings are also lower than the 90.6% reported in Ethiopia (Gebremariam et al, 2021) but higher than 67% to 77% in Uganda in 2019 (Sekandi et al, 2020b), 64.2% in Ethiopia in 2021 (Gashu et al, 2021), 56.5% in South Korea in 2021 (Bea et al, 2021), and 78.7% pooled prevalence from a systematic review conducted in Ethiopia in 2019 (Zegeye et al, 2019). This discrepancy may be attributed to differences in cultures, sample size, and settings.…”
Section: Discussioncontrasting
confidence: 82%
“…The 84.6% adherence rate observed in this study is lower than the 90% targeted by the national TB and leprosy program (USAID, 2022). Our findings are also lower than the 90.6% reported in Ethiopia (Gebremariam et al, 2021) but higher than 67% to 77% in Uganda in 2019 (Sekandi et al, 2020b), 64.2% in Ethiopia in 2021 (Gashu et al, 2021), 56.5% in South Korea in 2021 (Bea et al, 2021), and 78.7% pooled prevalence from a systematic review conducted in Ethiopia in 2019 (Zegeye et al, 2019). This discrepancy may be attributed to differences in cultures, sample size, and settings.…”
Section: Discussioncontrasting
confidence: 82%
“…Self-efficacy refers to an individual's perception of his or her competence to successfully perform a behavior ( 37 ). Multiple studies have shown that patients with chronic diseases (such as hypertension, type 2 diabetes, and tuberculosis) with higher levels of self-efficacy tend to have higher treatment adherence ( 38 42 ). Parents with higher scores on the self-efficacy dimension have the higher subjective initiative in improving children's medication adherence, so their children's medication adherence scores are relatively higher, which suggests that improving parents' self-efficacy may be an effective way to improve children's medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…TB participants with IGR and/or HIV received care as per Tanzania standard guidelines for collaborative care and control of TB/HIV and/or DM, which were integrated at the TB clinic [22]. Participants were evaluated by using self‐reporting and pills refill techniques [23] for monitoring expected treatment adherence (“expected” adherence to anti‐TB was defined by participants who took ≥95% of the prescribed anti‐TB drugs,) [24], and sputum smear conversion and/or sputum culture for all TB patients (newly and previously treated TB) was evaluated at 2 and 5–6 months of TB treatment. If sputum smears remained positive at 2 months of treatment, an Xpert MTB/RIF test was performed to rule out DR‐TB.…”
Section: Methodsmentioning
confidence: 99%